2018
DOI: 10.1111/jphp.12995
|View full text |Cite
|
Sign up to set email alerts
|

MiR-324-5p reduces viability and induces apoptosis in gastric cancer cells through modulating TSPAN8

Abstract: This study suggested a novel, probable mechanism of miR-324-5p in gastric cancer context and revealed that miR-324-5p inhibited gastric cancer cell survival by targeting TSPAN8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
(44 reference statements)
1
22
0
Order By: Relevance
“…MiRNAs participate in diverse molecular and cellular processes, such as cellular migration/invasion, cell growth, apoptosis and signal transduction. MiRNAs dysregulation is a hallmark of many cancers, including glioblastoma, and they can be classified into tumour‐suppressive miRNAs and onco‐miRNAs . For example, miRNA‐744 expression is strongly repressed in glioblastoma, causing elevated transforming growth factor 1 beta (TGFB1) and dishevelled 2 (DVL2) expression and increased tumour cell migration .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs participate in diverse molecular and cellular processes, such as cellular migration/invasion, cell growth, apoptosis and signal transduction. MiRNAs dysregulation is a hallmark of many cancers, including glioblastoma, and they can be classified into tumour‐suppressive miRNAs and onco‐miRNAs . For example, miRNA‐744 expression is strongly repressed in glioblastoma, causing elevated transforming growth factor 1 beta (TGFB1) and dishevelled 2 (DVL2) expression and increased tumour cell migration .…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs dysregulation is a hallmark of many cancers, including glioblastoma, and they can be classified into tumour-suppressive miRNAs and onco-miRNAs. [24][25][26][27][28] For example, miRNA-744 expression is strongly repressed in glioblastoma, causing elevated transforming growth factor 1 beta (TGFB1) and dishevelled 2 (DVL2) expression and increased tumour cell migration. [29] In contrast, up-regulation of miRNA-21 in glioblastoma is associated with suppression of phosphatase and tensin homolog (PTEN), as well as programmed cell death 4 (PDCD4) expression, causing enhancement of cell survival and inhibition of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to KLF3, miR-324-5p is also reported to regulate the expression of CUEDC2, 21 ELAVL1, 25 ETS1, 26 EZH2, 39 GLI1, 27 HMGXB3, 40 PKM2, 41 SCF β-TrCP E3 ligase, 42 SP1, 26 TSPAN8, 43 and WASF-2, 40 in turn eliciting downstream effects associated with these genes. KLF3 is an important regulator for the biological processes, including adipogenesis, erythropoiesis, and B cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that miR-324-5p can inhibit gallbladder carcinoma cell metastasis by downregulating the expression level of transforming growth factor β2 ( TGFB2 ), 19 as well as suppress the migration and induce the apoptosis of gastric cancer cells by inhibiting TSPAN8 . 20 Another study found that miR-324-5p can promote the osteogenic differentiation of human mesenchymal stem cells (MSCs) and murine C3H10T1/2 cells by regulating the Hedgehog signaling pathway. 21 Mesenchymal stem cells have the potential for myogenic differentiation, 22 indicating that miR-324-5p has a potential role in myogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%